Functional training versus Mat Pilates in motor and non-motor symptoms of individuals with Parkinson's disease: study protocol for a randomized controlled trial - Moratelli J.A.* (2022)
© 2022 Universidade Estadual Paulista - UNESP. All rights reserved.Aim: This study aims to compare a functional training protocol and Mat Pilates for individuals with Parkinson's disease and to evaluate the effects on motor symptoms, as well as non-motor symptoms using a randomized controlled trial. Methods: Protocol for a randomized clinical trial in which 45 individuals with Parkinson's disease will be recruited and randomly allocated to one of three groups: (1) functional training; (2) Mat Pilates; (3) control group. Both intervention groups will have 60 min classes twice a week for 12 weeks. The primary outcome will be analyzed through motor symptoms, including balance, mobility, muscle strength, handgrip strength, flexibility, range of motion, and cardiorespiratory fitness. Secondary outcomes will include non-motor symptoms such as cognition, aging perspective, mood, anxiety, and depression. Conclusion: This will be the first randomized trial to compare the effects of functional training and Mat Pilates in a population with Parkinson's disease. It is hypothesized that improvements in motor and non-motor symptoms will be greater and more lasting after functional training and Mat Pilates interventions than those that maintain their routine activities, given the benefits of exercise and the unprecedented protocols in this disease.